Governance at grassroots: Operation of Gram Sabha in Kerala and West Bengal - Mandal, Amal (2015)
Based on analytical investigation, this article reflects on the extent, nature and process of Gram Sabha in Kerala and West Bengal. Its main focus revolves around the interest evinced by the members concerned and the process and its impact. The central postulate is that despite conducive conditions and objective ambience, the operational experience of Gram Sabhas in the two states evinces that this grassroots institution is yet to culminate into one assembly of the villagers and for the villages. - Reproduced.
Keywords: Panchayat - India - West Bengal; Panchayat - India - Kerala; Panchayat